Design, fabrication and experimentation of swing electricity power generation system - Taweekun, Juntakan; Saba, arif; Mas, Fawzi; Asmuin, Nor Zelawati; Batcha, Mohd Faizal Mohideen; Noranai, Zamri (Science Publishing Corporation, 2018)
Energy need of today’s world is growing day by day because of consumption of larger extent of electricity due to growing population. Project is about generation of electricity by swing. Large number of children play in a playground, part of the power of their play caused by swing can be usefully harnessed resulting in significant energy storage. Yielded energy can be converted to electrical energy to be utilized for many applications. Oscillatory motion of swing is transferred to shaft attached, which further transfers its angular motion to rotary motion of the flywheel, rigidly connected at the end. The flywheel is connected to a generator by specific transmission to conserve and increase the speed at generator end. The generator converts the mechanical energy into electrical energy to be utilized for many applications. Current swing is able to generate enough electricity to power a 15 W DC fan and a 9 W DC bulb. The method provides a lowcost, low-resource means of electricity generation, especially for use in developing countries.